Reduction of COD in wastewater from an organized tannery industrial region by Electro-Fenton process - Kurt, Ugur; Apaydin, Omer; Gonullu, M. Talha (ELSEVIER SCIENCE BV, 2007)
Advanced oxidation processes (AOPs) have led the way in the treatment of aqueous waste and are rapidly becoming the chosen technology for many applications. In this paper, COD reduction potential of leather tanning industry wastewaters by Electro-Fenton (EF) oxidation, as one of the AOPs, was experimentally evaluated. The wastewater sample was taken from an outlet of an equalization basin in a common treatment plant of an organized tannery industrial region in Istanbul, Turkey. Treatment of the wastewater was carried out by an electrochemical batch reactor equipped with two iron electrodes, which were connected parallel to each other. The oxidation process was studied for optimization of H2O2 and the electricity consumptions were observed at different contact times under different pH conditions (3.0, 5.0 and 7.2). In each case, electricity consumption for decreased COD mass was estimated. In this process, COD was reduced by 60-70% within 10 min. By taking into consideration the local sewerage discharge limit, applicability of EF process for the tannery wastewaters was evaluated. (C) 2006 Elsevier B.V. All rights reserved.
Keywords: advanced oxidation processes; COD; electro-Fenton; iron electrodes; tannery wastewater; ELECTROCHEMICAL OXIDATION; STEEL ELECTRODES; DISPERSE DYES; ELECTROCOAGULATION; DESTRUCTION; REMOVAL; REACTOR; PHENOL; OXYGEN; Engineering; Environmental Sciences & Ecology